HARNESSING AI TO DEVELOP HOLISTIC HEALTHCARE PRACTITIONERS FOR A SUSTAINABLE FUTURE - RASHID1, SULTHAN AL; K K, VIGNESH; B, MADHUSUDHAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The integration of artificial intelligence (AI) in healthcare has revolutionized the way medical professionals diagnose, treat, and interact with patients (Mir et al., 2023). While AI's technical prowess is widely recognized, its ability to nurture holistic healthcare practitioners—those who address not only physical symptoms but also emotional, mental, social, and environmental determinants of health—presents an exciting frontier. Holistic healthcare is becoming increasingly important in addressing the complexities of modern medical practice, where patient-centered care, non-communicable diseases, and environmental factors interplay (Ambushe et al., 2023; Ernst, 2007; Samarasekera et al., 2025; Tsai & Yan, 2021).